2018
DOI: 10.1039/c7re00196g
|View full text |Cite
|
Sign up to set email alerts
|

Feed rate noise modulates autocatalysis and shapes the oscillations of the Belousov–Zhabotinsky reaction in a continuous stirred tank reactor

Abstract: Noise applied to a specific reactant feed rate directs the Belousov–Zhabotinsky reaction into specific pathways and results in noise-controlled oscillation shapes and features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…multipeaked periodic oscillations, bursting patterns, high sensitivity to small perturbations, or deterministic chaos [33][34][35] . It has recently been reported that feed rate noise can also modulate autocatalysis and shapes of the oscillations of the BZ reaction in CSTR 37 . Thus, coupling BZ-PISA with the CSTR operation of BZ holds great potential for achieving better control and consistency of both the self-assembled vesicles and their encapsulated cargo.…”
mentioning
confidence: 99%
“…multipeaked periodic oscillations, bursting patterns, high sensitivity to small perturbations, or deterministic chaos [33][34][35] . It has recently been reported that feed rate noise can also modulate autocatalysis and shapes of the oscillations of the BZ reaction in CSTR 37 . Thus, coupling BZ-PISA with the CSTR operation of BZ holds great potential for achieving better control and consistency of both the self-assembled vesicles and their encapsulated cargo.…”
mentioning
confidence: 99%
“…These, in turn evolve in a morphology sequence controlled by the chemical nature of the PISA reaction and the environment into which it takes place. Furthermore, since chemical reactions can be thought of as events of molecular recognition 25 one can begin to envisage [26][27][28][29] how PISA can potentially enable an extraordinary scenario for molecules recognizing molecules and use the sequences into which these molecules react to build material structures which can accomplish tasks or functions in a programmed fashion.…”
Section: Introductionmentioning
confidence: 99%
“…SR is also widely used in the fields of chemistry [21], biology [22], and physics [23,24]. In the field of neuroscience [25], a single neuron model is the basis for studying the biological and electrical properties of neurons.…”
Section: Introductionmentioning
confidence: 99%